The transition from radical prostatectomy to prostate carcinoma in men - Miguel de Sousa Carvalho, Jorge (2011)
The experience of an oncological disease itself involves a great personal challenge. Thus, the male patient with prostate cancer undergoing radical prostatectomy experience a set of changes, translated through a process of transition. This research study aimed to understand the transition of male patient with prostate cancer undergoing radical prostatectomy. We developed a qualitative, descriptive and exploratory research, using a semi-structured interview for data collection and a content analysis for the decomposition of data by microanalysis, through interviews with 18 participants. From the data analysis, it is observed that man experiences a long transition process starting from the route to diagnosis, through several stages until the possible self-restructuring. It was possible from this study, to know the transition process, to understand the needs, to describe the resources used and to know the perspective on the role of the nurse male patient with prostate cancer undergoing radical prostatectomy.